2004
DOI: 10.1111/j.1440-1681.2004.04089.x
|View full text |Cite
|
Sign up to set email alerts
|

Captopril Reverses the Reduced Vasodilator Response to Bradykinin in Hypertensive Pregnant Rats

Abstract: 1. Pregnancy in rats is characterized by a reduction in arterial pressure that is associated with a decreased response to vasoconstrictors. However, the responses to vasodilators in isolated vessels remain controversial and are not well established in hypertensive pregnant rats. 2. In the present study, we investigated the effect of pregnancy on the bradykinin (BK)-induced vasodilator responses of the isolated mesenteric arterial bed (MAB) from Wistar normotensive and spontaneously hypertensive rats (SHR) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…34 We have demonstrated in this study that the vasodilator responses induced by both Ang II and Ang-(1-7) were similar in MAB from W-P and W-NP rats. This data confirm previous findings showing the NO-dependent vasodilator effect of bradykinin and acetylcholine, 35 suggesting that endothelial function is not changed during the adaptations of normal pregnancy. However, we demonstrate that the vasodilator responses induced by Ang II and Ang-(1-7) were higher in MAB from SHR-P than in SHR-NP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…34 We have demonstrated in this study that the vasodilator responses induced by both Ang II and Ang-(1-7) were similar in MAB from W-P and W-NP rats. This data confirm previous findings showing the NO-dependent vasodilator effect of bradykinin and acetylcholine, 35 suggesting that endothelial function is not changed during the adaptations of normal pregnancy. However, we demonstrate that the vasodilator responses induced by Ang II and Ang-(1-7) were higher in MAB from SHR-P than in SHR-NP.…”
Section: Discussionsupporting
confidence: 93%
“…This response appears to be specific to the peptides of RAS because previous studies demonstrated a reduction in the vasodilator response induced by bradykinin in mesenteric arteries from SHR-P compared to SHR-NP while acetylcholine and nitroglycerin vasodilator responses appear to be similar among the groups. 35 Overall, these data suggest an important contribution of RAS on the hemodynamic changes and BP reduction during pregnancy in genetically hypertensive rats.…”
Section: Discussionmentioning
confidence: 95%
“…Maeso et al (1998) provided evidence that diminished EDHF is likely to account for the reduced relaxation to ACh associated with aging in mesenteric vasculatures from SHR and that the enhancement of ACh-induced relaxations by losartan seems to be dependent of increased NO availability. In the isolated mesenteric arterial bed from pregnant SHR, vasodilator responses to bradykinin were less than those from nonpregnant SHR, and captopril potentiated the bradykinin action and abolished the differences between pregnant and nonpregnant SHR; bradykinin-induced vasodilatation was reduced by L-NAME and was abolished in the presence of L-NAME plus high K ϩ solution (Resende et al, 2004). It was concluded that increased ACE activity may be involved in the pregnancy-associated reduction in vascular responses to bradykinin in the mesenteric arteries of hypertensive rats and that the vasodilatation seems to be mediated by NO and EDHF.…”
Section: G Mesenteric Vasculaturementioning
confidence: 96%
“…The levels obtained from pregnant hypertensive rats were not significantly different from those obtained from the normotensive groups, which were in agreement with previous findings. 15,16,21 These results might be partially explained by an increased production of NO and prostacyclin from vascular endothelium 20 and a hyporeactivity to vasoconstrictors, 34 which may contribute to vasodilation and consequent reduction in peripheral vascular resistance. Although a specific role for NO in the induction of hemodynamic alterations in pregnancy is somewhat controversial, it is widely accepted that an excess of NO is generated by endothelial cells during normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Conversely, the responsiveness to vasodilators such as bradykinin is decreased in resistance arteries of pregnant SHRs 21 as well as in small subcutaneous arteries and myometrial resistance arteries from women with preeclampsia. 22,23 Because bradykinin endothelium-dependent relaxation is mediated by NO and endothelium-derived hyperpolarizing factor, these findings suggest that endothelial dysfunction may contribute to the altered vasoreactivity seen in pregnant SHRs, 21 to preeclampsia and to decreased placental perfusion and its associated intrauterine growth restriction. 24 The endothelium has a key role in maintaining blood fluidity and in preventing thrombus formation.…”
Section: Introductionmentioning
confidence: 94%